Three-dimensional natural color imaging based on focus level correlation algorithm using structured illumination microscopy - Wang, Mengrui; Zhao, Tianyu; Wang, Zhaojun; Feng, Kun; Ren, Jingrong; Liang, Yansheng; Wang, Shaowei; Lei, Ming (Frontiers in Physics, 2022)
Taking advantages of high-resolution, natural color restoration, and high imaging speed, optical sectioning structured illumination microscopy (OS-SIM) plays an important role in geology, biology, and material science. However, when encountering chromatic aberration or dealing with samples with semitransparent surface, the HSV decoding algorithm suffers intensity deviation and fading color. In this paper, we propose a focus level correlation algorithm for 3D color image reconstruction in OS-SIM. Simulations and experiments demonstrate that the algorithm can restore color of sample authentically, and improves the image processing speed by about 45%. This new algorithm successfully improve the results and the speed of optical sectioning reconstruction, expanding the application of OS-SIM.